2020
DOI: 10.1093/hmg/ddaa199
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant early growth of individual trigeminal sensory and motor axons in a series of mouse genetic models of 22q11.2 deletion syndrome

Abstract: We identified divergent modes of initial axon growth that prefigure disrupted differentiation of the trigeminal nerve (CN V), a cranial nerve essential for suckling, feeding and swallowing (S/F/S), a key innate behavior compromised in multiple genetic developmental disorders including DiGeorge/22q11.2 Deletion Syndrome (22q11.2 DS). We combined rapid in vivo labeling of single CN V axons in LgDel+/− mouse embryos, a genomically accurate 22q11.2DS model, and 3-dimensional imaging to identify and quantify phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 63 publications
2
15
0
Order By: Relevance
“…We have begun to assess interactions between neural crest and placodal cells underlying development of cranial somatosensory ganglia. The dual origin of cranial ganglion sensory neurons, as well as their divergent fates -primarily mechanoreceptive for placode descendants, nociceptive for those from the neural crest (D' Amico- Martel and Noden, 1983) -is well established, and our analyses in the mouse (Karpinski et al, 2016;Maynard et al, 2020a;Motahari et al, 2020) confirmed and extended earlier studies. Using transcriptional lineage tracing, we identified diversity within the neural crest population (Figure 4).…”
Section: Other Cranial Neural Crest Cells and Other Cranial Nervessupporting
confidence: 85%
See 4 more Smart Citations
“…We have begun to assess interactions between neural crest and placodal cells underlying development of cranial somatosensory ganglia. The dual origin of cranial ganglion sensory neurons, as well as their divergent fates -primarily mechanoreceptive for placode descendants, nociceptive for those from the neural crest (D' Amico- Martel and Noden, 1983) -is well established, and our analyses in the mouse (Karpinski et al, 2016;Maynard et al, 2020a;Motahari et al, 2020) confirmed and extended earlier studies. Using transcriptional lineage tracing, we identified diversity within the neural crest population (Figure 4).…”
Section: Other Cranial Neural Crest Cells and Other Cranial Nervessupporting
confidence: 85%
“…Individual trigeminal motor axons, as well as primarily placodal derived trigeminal sensory axons, respond differently as they interact with neural crest derived mesenchymal substrates in the periphery whose A-P identity has been presumably altered by enhanced RA signaling in the anterior rhombomeres. December 2020 | Volume 11 | Article 610970 the posterior shift of rhombomere patterning, based upon ectopic RA-regulated gene expression, is far more prominent than that in LgDel, as is disruption of CN V differentiation (Motahari et al, 2020). We confirmed the RA-dependence of this hindbrain patterning change in LgDel and its relationship to initial cranial nerve dysmorphology via genetic rescue of the anomalous RA-dependent shift in patterning.…”
Section: Swallow Hard: Does the Face Predict The Brain And Behavior Fsupporting
confidence: 61%
See 3 more Smart Citations